6n+9=-3n-27

Simple and best practice solution for 6n+9=-3n-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n+9=-3n-27 equation:


Simplifying
6n + 9 = -3n + -27

Reorder the terms:
9 + 6n = -3n + -27

Reorder the terms:
9 + 6n = -27 + -3n

Solving
9 + 6n = -27 + -3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '3n' to each side of the equation.
9 + 6n + 3n = -27 + -3n + 3n

Combine like terms: 6n + 3n = 9n
9 + 9n = -27 + -3n + 3n

Combine like terms: -3n + 3n = 0
9 + 9n = -27 + 0
9 + 9n = -27

Add '-9' to each side of the equation.
9 + -9 + 9n = -27 + -9

Combine like terms: 9 + -9 = 0
0 + 9n = -27 + -9
9n = -27 + -9

Combine like terms: -27 + -9 = -36
9n = -36

Divide each side by '9'.
n = -4

Simplifying
n = -4

See similar equations:

| y=0.25(x-5)(x-1) | | (x)(x)+3x+2= | | ydx-(3x-y^3)dy=0 | | 2.3x+14= | | n/3=5n-42 | | (p/2)/2 | | 3+3=8x+23 | | (x)(x)-11x+18=0 | | 3/2y-8=-5 | | 7x+20=3x+36 | | 2x+9=2x+3 | | x^2=5y+35 | | 4+3x=6x-83x-12 | | -3x+5(-6x+4)-(-30x+16)=-9(x-5) | | 9k^2+29k+8=0 | | 16x-22x=1/2 | | 6p+11=3p-4 | | 6z-5=3z-4 | | 16x/-22x=1/2 | | X-80=100 | | 6/7y=-18/77 | | 5/7x-3=2 | | -0.1x+4=11 | | 2x-(5x+9)=6(2x+1) | | -2(4x+1)+3x-7=2(x+2)+7x-1 | | 6/7y=18/77 | | y/5-1=0 | | 60x^3-30x^2=o | | 1000=2x+0.5y | | A-99=100 | | 0.7(5x+7)=2.0-(x-3) | | x^2+y^2=81-8x^2-8y^2 |

Equations solver categories